The Agavaceae: Taxonomic and Phylogenetic Appraisal - R.M.Pai2, D.A.Patil1* and (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> A comparative assessment of the Agavaceae from the standpoint of taxonomy and phylogeny is attempted in the light of different disciplines of morphology. The agavoids are apparently a diverse assemblage, but brought under one roof by important phyletic parameters such as karyomorphology, stomatal nature, pollen structure, perianth anatomy and androecial morphology, etc. Polyphylesis is evident in the evolution of the group. The agavoids seem to have arisen from ancient liliaceous stocks. They do not appear to be the progenitors of any of the higher data of petaloid monocotyledons. The present authors are inclined to treat the agavoids best under four distinct taxonomic entities viz., Agaveae, Phormieae, Doryantheae and Dracaeneae under the Agavaceae. Hosta is regarded as a ‘half-way house’ between the lilies and agavoids.